Profil Penyakit Jantung Bawaan Sianotik di Rumah Sakit Umum Daerah Dr. Soetomo Surabaya - Alverina, Clara; Utamayasa, I Ketut Alit; Sembiring, Yan Efrata (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2022)
Introduction. Cyanotic congenital heart disease (CHD) is an abnormality of the heart that causes blood with low oxygen content to circulate directly to the body.Objective. To evaluate the profile of cyanotic congenital heart disease at Dr. Soetomo General Hospital Surabaya.Methods. This is a descriptive study using medical records of cyanotic CHD patients aged ≤18 years old from June 2018 – May 2020. Gender, age, nutritional status, sign and symptom, type of cyanotic CHD, complication and treatment were taken as the variables.Result. Out of 116 patients in this study, the majority were male (58.62%). Most patients first diagnosed at the age of 0 – less than 1 year (76.72%) with normal nutritional status (51.72%). Tetralogy of Fallot (TOF) is the most common type (42.24%). Murmur was the most common sign and symptom (92.24%). Frequently observed complications were pneumonia (37.07%).Conclusion. Patients with cyanotic CHD are mostly male, diagnosed at the age of 0 – less than 1 year with normal nutritional status. TOF is the most common type. Most patients present with murmurs. Predominant complication is pneumonia.